Obstacles school-going female adolescents in Gweru face in translating HIV/AIDS knowledge and attitudes into HIV preventive sexual behaviours - Mugari, Sipikelelo (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.